Varicose veins of lower extremities: methodical recommendations for students of higher medical education in the discipline of «Surgery» Faculty of Medicine [Electronic edition] - Oklei, D.V.; Bychkov, S.O.; Pronin, V.O.; Оклей, Денис Вікторович; Бичков, Сергій Олександрович; Пронін, Василь Олександрович (Kharkiv : V. N. Karazin Kharkiv National University, 2023)
Methodical recommendations are worked out on the basis of the Programs of disciplines of «Surgery» for students of higher medical educational institutions of III–IV levels of accreditation, authorized by Ministry of Health of Ukraine. These recommendations are intended for the 5 th year English-speaking medical students.
Варикозне розширення вен нижніх кінцівок : методичні рекомендації для здобувачів вищої медичної освіти з дисципліни «Хірургія» [Електронне видання]
Електронне навчальне видання комбінованого використання. Можна використовувати в локальному та мережному режимі
Keywords: Research Subject Categories::MEDICINE; MEDICINE::Surgery::Vascular surgery; lower extremities; clinical physical examination; additional examination methods; differential diagnostics; treatment strategy; surgical treatment; prophylaxis; varicose veins; нижні кінцівки; хірургія; профілактика; клінічний огляд; стратегія лікування; додаткові методи обстеження; диференціальна діагностика; варикозне розширення вен